Factors Predicting Febrile Urinary Tract Infection After Ureterorenoscopic Lithotripsy in Pediatric Patients - Evren, Ismail; Sam, Emre (European Journal of Therapeutics, 2023)
Introduction: There is no study investigating the factors predicting postoperative febrile urinary tract infection (fUTI) in pediatric patients. We aimed to determine the factors predicting postoperative fUTI in pediatric patients who underwent ureterorenoscopic lithotripsy (URS-L). Methods: Pediatric patients who underwent URS-L due to ureter or kidney stones in our clinic between 2012 and 2019 were analyzed retrospectively. The demographic data, stone characteristics, intraoperative and postoperative data of those with and without postoperative fUTI were compared. Univariable and multivariable binary logistic regression analysis was performed to determine predictors of fUTI. Results: A total of 136 patients were included in the study. Postoperative fUTI developed in 17 patients (12.5%). History of stone surgery, history of UTI, presence of nephrostomy/D-J stent, type of surgery, operation time, length of stay, and presence of complication except fUTI were found to be significantly different in the fUTI group. In the univariate analysis, history of stone surgery, history of UTI, presence of nephrostomy/D-J stent, type of surgery, operation time, and presence of complication except fUTI were determined as factors predicting fUTI. In multivariate analysis, only the history of UTI was identified as an independent predictive factor. Conclusion: In pediatric patients, infectious complications constitute the majority of complications after URS-L. History of UTI is the only independent factor that predicts postoperative fUTI after URS-L.